Maternal-newborn nursing demystified : - Johnson, Joyce (McGraw-Hill Education, 2010)
Maternity Nursing Demystified delivers a detailed, easy-to-follow overview of the essential concepts involved in providing nursing care to the mother and child before, during, and after pregnancy. The book emphasizes the underlying factors involved in maintaining or restoring the health of mother and new born and discusses the various factors that may threaten their wellbeing. You’ll also learn how to apply these concepts to real-life situations.